Frequency of Ureteral Stent Encrustations in a Urology Unit of Tertiary Care Hospital - Muhammad Akhtar, Hafiz Muhammad Usman, Muhammad Hamza Khan Lodhi, Zeeshan Zafar, Muhammad Saad Ullah, Muhammad Umar Khan, Mm Khan (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of encrustations of ureteral stents in a tertiary care hospital of Pakistan. Patients and Methods: In this study we included 150 patients of Urology Unit of Ibn e Sina Hospital and Research Institute Multan, Pakistan in whom ureteral stents implantation was done. The study duration was April-2020 to July-2020. Patients with ureteral stents having renal stone, ureteric stone, ureteral stricture, pelviureteric junction obstruction (PUJO), trauma or malignant disease as primary pathology and duration of implantation >2 weeks to <2 years were included. Results: Mean age of patients included in this study was 46.46±12.26 years. Mean duration of stent placement was 11.96±6.01 weeks. There were 97 (64.7%) male and 53 (35.3%) female patients. There were 72 (48%) patients with renal stone disease, 32 (21.33%) patients with ureteric stone, 11 (7.33%) patients with pyeloplasty, 22 (14.67%) patients with partial nephrectomy and 13 (8.67%) patients with obstruction sec. to malignancy were included in this study. Stent encrustation was diagnosed 52 (34.67%) patients. Conclusion: After implantation, ureteral stent encrustation is still a cause for concern for urologists. Because its encrustation management may involve additional urologic procedures. In present study, stent encrustation was found in 62 (32.29%) patients. Keywords: Double-J stents, stent encrustation.